2007
DOI: 10.1055/s-0037-1616583
|View full text |Cite
|
Sign up to set email alerts
|

A novel radiographic method to facilitate measurement of the tibial plateau angle in dogs

Abstract: The tibial plateau levelling osteotomy (TPLO) is commonly performed for treatment of cranial cruciate ligament deficiency in dogs. In order to be performed as described, this procedure relies on consistent measurement of the tibial plateau angle (TPA) on radiographs. This prospective study compared two radiographic methods for subsequent TPA measurement with respect to measured angle and ease of determining landmarks for measurement as determined by four observers. One method was the accepted standard radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported significant intra‐ and inter‐observer differences in TPA measurements using radiography (Caylor et al., 2001; Fettig et al., 2003). One of the major factors affecting TPA measurement is the difference in the understanding and selection of anatomical landmarks for TPA measurement by each observer (Headrick et al., 2007). In the present study, the mean TPA measurement obtained using the CT method was not significantly different from that obtained using the radiographic method, but the CT method showed higher intra‐ and inter‐observer agreement than the radiographic method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported significant intra‐ and inter‐observer differences in TPA measurements using radiography (Caylor et al., 2001; Fettig et al., 2003). One of the major factors affecting TPA measurement is the difference in the understanding and selection of anatomical landmarks for TPA measurement by each observer (Headrick et al., 2007). In the present study, the mean TPA measurement obtained using the CT method was not significantly different from that obtained using the radiographic method, but the CT method showed higher intra‐ and inter‐observer agreement than the radiographic method.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the outcomes of TPLO, it is essential to optimise the consistency and repeatability of TPA measurements, as well as the ease of landmark identification (Headrick et al., 2007). However, positioning of the tibia during radiography may affect the appearance of anatomic landmarks used for the determination of the TPA, and observers subjectively select the anatomic landmarks; therefore, measurement variability may be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Biologic options for partial joint arthroplasty in small animals include osteochondral autografts and osteochondral allografts. Whereas osteochondral autograft treatment for osteochondrosis lesions has been reported by Dr. Noel Fitzpatick 10 and our group, 11 no peer‐reviewed literature has been published and this technique is currently limited to treatment of focal defects. We have also presented data regarding the use of an osteochondral allograft for hemi joint arthroplasty for a congenital elbow derangement in 1 dog 12 .…”
Section: The Near Futurementioning
confidence: 99%